Corelational Analysis between the Occupational Competency Assessment and Early Return to Work in Upper Extremity Injuries - Rongzhou ZHONG; Jianing XU; Jian DONG; Xiaoyu SHI; Taoli WANG; Longzhu HUANG; Huifang WANG (康复学报)
Objective:To study the correlation between occupational ability of upper limbs in patients with upper extremity injuries and whether or not early return to work (RTW), in order to find the occupation-related functions as an aim of upper limb rehabilitation of injury workers and to find some universal occupation-related functions which can be quantified as the goals of the rehabilitation training.Methods:From January 2014 to December 2015, 101 patients who admitted to our hospital with upper extremity injuries were included in this study. Their occupational abilities such as pushing, pulling, lifting and carrying were measured by Baltimore Therapeutic Equipment (BTE) on admission and before discharge. Six weeks for a course, they were trained two hours one day for general vocational training and twenty minutes per session, twice one day for BTE training and two hours one day for hand function. All of them had been trained for six weeks. After three months, the result of their return to work or not was investigated and the correlation between return to work and the occupation-related function was analyzed.Results:After professional ability rehabilitation, all patients'occupational competency, such as pushing, pulling, lifting and carrying, was significantly improved (P<0.05). The dynamic transporting competency, right hand carrying capacity and right hand pail capacity of patients who return to work after three months were more improved than those who did not return to work (P<0.05). The values about right hand carrying capacity and right hand pail capacity were significantly correlated with the RTW (P<0.01).Conclusion:The dynamic transporting competency, right hand carrying capacity, and right hand pail capacity can be used as universal occupation-related functions that can be quantified and rehabilitation objectives.